Effects of opioids on local anesthesia in the rat: a codeine and tramadol study - Talita Girio Carnaval; Roberta Moura Sampaio; Camila Bernadeli Lanfredi; Maria Aparecida Borsatti; Carlos Alberto Adde (Sociedade Brasileira de Pesquisa Odontológica, 2013)
Opioids are central analgesics that act on the CNS (central nervous system) and PNS (peripheral nervous system). We investigated the effects of codeine (COD) and tramadol (TRAM) on local anesthesia of the sciatic nerve. Eighty Wistar male rats received the following SC injections in the popliteal fossa: local anesthetic with epinephrine (LA); local anesthetic without vasoconstrictor (LA WV); COD; TRAM; LA + COD; LA + TRAM; COD 20 minutes prior to LA (COD 20' + LA) or TRAM 20 minutes prior to LA (TRAM 20' + LA). As a nociceptive function, the blockade was considered the absence of a paw withdraw reflex. As a motor function, it was the absence of claudication. As a proprioceptive function, it was the absence of hopping and tactile responses. All data were compared using repeated-measures analysis of variance (ANOVA). Opioids showed a significant increase in the level of anesthesia, and the blockade duration of LA + COD was greater than that of the remaining groups (p < 0.05). The associated use of opioids improved anesthesia efficacy. This could lead to a new perspective in controlling dental pain.